Mobilitas Cerdas dalam Kerangka Kota Pintar: Penilaian Dampak Sosial Transformasi Digital di Kawasan Perkotaan Indonesia - Tanjung, Abda’u; Nurmandi, Achmad; Fridayan, Helen Dian; Chiang, Li-Chun (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
Rapid urbanization and population growth in Indonesia have intensified challenges in urban mobility, particularly traffic congestion and the inefficiency of public transportation systems. In response, the concept of smart mobility, embedded within the broader smart city framework, has emerged as a technologically and policy-oriented strategy. This study aims to examine the social impacts of digital transformation in urban mobility across major Indonesian cities by employing the smart mobility indicators developed by Giffinger, which include local accessibility, (inter)national accessibility, the availability of ICT infrastructure, and the presence of sustainable, innovative, and safe transportation systems. Using a qualitative research design, this study analyzes 179 online news articles and academic publications relevant to these four indicators, supported by data analysis tools such as NVivo 12 Plus and crosstab visualizations. The findings demonstrate that digital mobility transformation has significantly influenced societal behavior, enhanced inclusivity in transportation services, and improved the overall quality of life for urban residents. Cities such as Jakarta, Surabaya, and Semarang exhibit more advanced implementations of smart mobility, whereas other regions continue to face barriers related to infrastructure disparities, digital literacy limitations, and insufficient stakeholder collaboration. Furthermore, despite notable progress, the study identifies emerging challenges, including persistent digital inequality and weak integration between local governments and private-sector actors. The study concludes that the success of smart mobility initiatives depends not only on technological readiness but also on institutional capacity, equitable access, and active community participation.